Policing Domestic Violence in the Post-SARP Era: the Impact of a Domestic Violence Police Unit - Exum, Myron Lyn (Crime & delinquency, 2014)
During the Spousal Assault Replication Program, the city of Charlotte, North Carolina, was identified as a site where arrest did not deter misdemeanor domestic violence. Shortly after these findings were published, the Charlotte-Mecklenburg Police Department developed a Domestic Violence (DV) unit to combat the problem of intimate partner violence. The mission of the Charlotte DV unit is to reduce future offending through intensive investigation and victim assistance. The current study evaluates the impact of the Charlotte DV unit versus standard patrol on official accounts of offender recidivism in a random sample of 891 domestic violence cases. Controlling for offender demographics, prior criminal history, case severity, and additional criminal justice responses, suspects processed through the DV unit had significantly lower rates of re-offending across an 18- to 30-month follow-up period. Theoretical explanations for the DV unit effect are proposed.